Relationship Between Cystatin C and Coronary Artery Atherosclerosis Progression Differs by Type 1 Diabetes - Maahs, David M. (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Cystatin C has been proposed to better estimate renal function and predict cardiovascular disease (CVD) than serum creatinine. To expand on our previous report, we investigated whether the relationship of cystatin C to progression of coronary artery atherosclerosis (CA) differed between individuals with type 1 diabetes (T1D) and persons without diabetes. METHODS: Coronary artery calcium was measured twice over 2.4 ± 0.4 years (n = 1,123, age = 39 ± 9 years, 47% male, 45% T1D). Significant CA progression was defined as a ≥2.5 increase in square root calcium volume score or development of clinical coronary artery disease. Stepwise multiple logistic regression was performed to investigate whether the association of cystatin C to CA progression differed by T1D status. RESULTS: The main finding and novelty of this article is that while the univariate association of cystatin C to CA progression was similar in T1D patients and persons without diabetes mellitus and in the expected direction (increased cystatin C as a biomarker of worsening renal function associated with CA progression), the association of cystatin C to progression of CA differed by T1D status (P = 0.01) after adjustment for other CVD risk factors. Unexpectedly, in persons without diabetes mellitus having relatively normal renal function, increased cystatin C was associated with decreased CA progression (odd ratio [OR] = 0.65, 95% confidence interval 0.44–0.96, P = 0.029) after adjustment, primarily due to adjustment for body mass index (BMI). Removal of BMI from this model resulted in a 49% change in the OR. CONCLUSIONS: Our hypothesis-generating data suggest a complex relationship among cystatin C, BMI, and CA progression that requires further study.